Pengaruh Metode Thinking Aloud Pair Problem Solving (TAPPS) Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP Negeri 9 Pematangsiantar - Hosea Togatorop; Christa Voni R Sinaga; Gayus Simarmata (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to determine the effect of the Thinking Aloud Pair Problem Solving (TAPPS) method on the mathematical communication skills of class VIII students at SMP Negeri 9 Pematangsiantar after applying the Thinking Aloud Pair Problem Solving (TAPPS) method. The type of research used is experimental research. In this research the author used a quantitative approach. The design used in this research is One Group Pretest-Posttest Design. This research involved an experimental class that was treated with the Thinking Aloud Pair Problem Solving (TAPPS) learning method and then given pre-test and post-test treatment to draw conclusions. For more details, see table 3.1 below. The research results obtained showed that the Thinking Aloud Pair Problem Solving (TAPPS) method had an influence on students' mathematical communication skills, reaching an average pre-test score in the Experiment class of 48.63, while the average score was 48.63. Post-test average in the Experiment class was 78.63. This proves that the Experimental class has further improved abilities after being given treatment using the TAPPS Method.